2022
DOI: 10.1007/s40670-022-01714-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Students’ Motivation in Relation to Asynchronous Anatomy Video Lectures

Abstract: Objectives This study aimed to investigate medical students’ motivation in relation to asynchronous anatomy video lectures, carried out during COVID-19 remote teaching. Methods Repeated cross-sectional modified Instructional Materials Motivation Survey questionnaire, validated in Brazil, was applied to 255 students attending the first semester of the undergraduate medical course at the José do Rosário Vellano University, in June 2020 and November 2020. The data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…25,[43][44][45][46] As noted above, our students recognize the importance of face-to-face in-person interactions, but are also receptive to the benefits of a multimodal approach to teaching and learning brought about by the COVID-19 pandemicparticularly how a blended curriculum can create an environment that is conducive to a wider range of students, largely aligning with the findings of Totlis et al 16 Students also suggested ways in which this could be improved (e.g., smaller classes, increased clinical relevance, and access to interactive research) but flexibility of learning modalities and the option to access material online is one way that we can maintain the benefits of in-person education and draw upon learnings from the responses to the COVID 19 pandemic. 17,19,39,47 The blended learning environment has a number of advantages, including a positive effect on student grades and motivation, as well as retaining some in-person learning, for example, for laboratories. 19,39,48 Our anatomy program for science students has continued to evolve over recent years, with inperson lectures and laboratories increasingly being complemented by a suite of online resources.…”
Section: Discussionmentioning
confidence: 99%
“…25,[43][44][45][46] As noted above, our students recognize the importance of face-to-face in-person interactions, but are also receptive to the benefits of a multimodal approach to teaching and learning brought about by the COVID-19 pandemicparticularly how a blended curriculum can create an environment that is conducive to a wider range of students, largely aligning with the findings of Totlis et al 16 Students also suggested ways in which this could be improved (e.g., smaller classes, increased clinical relevance, and access to interactive research) but flexibility of learning modalities and the option to access material online is one way that we can maintain the benefits of in-person education and draw upon learnings from the responses to the COVID 19 pandemic. 17,19,39,47 The blended learning environment has a number of advantages, including a positive effect on student grades and motivation, as well as retaining some in-person learning, for example, for laboratories. 19,39,48 Our anatomy program for science students has continued to evolve over recent years, with inperson lectures and laboratories increasingly being complemented by a suite of online resources.…”
Section: Discussionmentioning
confidence: 99%